The Psychological factors to engage in Prostitution: A Study in Karawang, Indonesia. - Putrie Dimala, Cempaka; Mubina, Nuram (International Journal of Psychosocial Rehabilitation, 2020)
The commercial sex worker is a profession aimed at earning money or goods by self-employed in sexual activity. Women who choose to be a commercial sex worker usually have problems that are considered difficult to handle and they have their own reason to underlie its decision. Researchers are trying to see what factors behind the women choose to work as a commercial sex worker and how the underlying decision form, so as to describe the profile of a woman who decides to work as a commercial sex worker. The method used in this study is qualitative phenomenology. Data collection techniques are conducted through interviews and observations. The data obtained is then analyzed through the reduced verbatim transcript, found the meaning unit, then brings up the essential themes in the participant experience, then the data is verified and drawn conclusions. The results showed that in the process both subjects had quite different reasons in which he chose the work, where for the subject of one more decision based on rational thought. As for the subject, two more decisions are based on intuition.